Developing Reading Competencies of College Students Using Blended Instruction - Akut, Katherine; Abejuela, Hazel Jean M. (International Journal of Language and Literary Studies, 2020)
Developing 21st-century reading competencies is one of the primary concerns of higher education institutions (HEIs). Initiatives have been undertaken to prepare the learners to function effectively in this technology-driven society. Hence, academic institutions integrate technology and the Internet in the teaching-learning processes. This study intends to determine the effectiveness of instructional material on developing reading competencies using blended instruction. Dziuban, Hartman and Moskal, (2004) define blended instruction as a pedagogical approach that integrates the effectiveness and socialization opportunities of the classroom with the technologically enhanced active learning possibilities of the online environment. Six lessons were implemented in the English 107 – College Reading Skills classes. The learners were provided with hypertext reading activities, individual and collaborative tasks, online discussions, online surveys and other extension activities which provided them with the opportunity to communicate their ideas on the topics discussed in class. To determine the effectiveness of the lessons, a one-group pretest and post-test design was used. The pre-test and post-test scores were compared using the paired t-test. Findings reveal that the students performed better after the implementation of the lessons in developing reading competencies using blended instruction. Moreover, the majority of the students said that the lessons are interesting, meaningful, useful and enjoyable. It can be concluded that blended instruction effectively develops the students’ reading competencies.